Kajian Yuridis Pertanggungjawaban Hukum dalam Tindak Pidana Penadahan - Samsuto Samsuto; Yasmirah Mandasari Saragih; Biner Sihotang (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the construction of criminal liability in the crime of handling stolen goods, focusing on situations where the perpetrator purchases or receives goods without knowing they are the result of a crime, especially when the economic value is relatively small, i.e., below Rp5,000,000. This normative study uses a legislative approach by examining Article 591 of Law Number 1 of 2023 on the Criminal Code (KUHP), as well as a conceptual approach to the theory of fault (schuld) and the principle of proportionality. The study's findings show that in transactions involving low-value goods, proving the subjective element of